Guide to U.S. foreign policy a diplomatic history - McMahon, Robert J., 1949-; Zeiler, Thomas W. (CQ Press, 2012)
Spanning the entire history of American diplomacy-- from the First Continental Congress to the war on terrorism to the foreign policy goals of the twenty-first century-- Guide to U.S. Foreign Policy traces not only the growth and development of diplomatic policies and traditions but also the shifts in public opinion that shape diplomatic trends. This comprehensive two-volume reference shows how the United States gained "the strength of a giant" and also analyzes key world events that have determined the United States' changing relations with other nations.